2018
DOI: 10.1016/j.pbi.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Wheat seed transcriptome reveals genes controlling key traits for human preference and crop adaptation

Abstract: Analysis of the transcriptome of the developing wheat grain has associated expression of genes with traits involving production (e.g. yield) and quality (e.g. bread quality). Photosynthesis in the grain may be important in retaining carbon that would be lost in respiration during grain filling and may contribute to yield in the late stages of seed formation under warm and dry environments. A small number of genes have been identified as having been selected by humans to optimize the performance of wheat for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Currently, molecular markers based on DNA analysis are widely used for genotyping and genetic identification in various crops (Shavrukov, 2016; Jatayev et al, 2017; Scheben, Batley & Edwards, 2017; Burridge et al, 2018). The application of molecular markers was successful in the study of wheat genes controlling such traits as 1,000-grain weight, protein and gluten content (Zhang et al, 2018), grain hardness (Nirmal et al, 2016), flour production from grain milling (Nirmal et al, 2017), and bread quality (Henry, Furtado & Rangan, 2018). Genome editing using CRISPR/Cas9 technology represents a novel method in plants (Khlestkina & Shumny, 2016; Liang et al, 2018; Borisjuk et al, 2019), for production of wheat with low gluten content (Sánchez-León et al, 2018), as required by people allergic to some components of gliadin in traditional wheat cultivars (Palosuo et al, 2001; Pastorello et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, molecular markers based on DNA analysis are widely used for genotyping and genetic identification in various crops (Shavrukov, 2016; Jatayev et al, 2017; Scheben, Batley & Edwards, 2017; Burridge et al, 2018). The application of molecular markers was successful in the study of wheat genes controlling such traits as 1,000-grain weight, protein and gluten content (Zhang et al, 2018), grain hardness (Nirmal et al, 2016), flour production from grain milling (Nirmal et al, 2017), and bread quality (Henry, Furtado & Rangan, 2018). Genome editing using CRISPR/Cas9 technology represents a novel method in plants (Khlestkina & Shumny, 2016; Liang et al, 2018; Borisjuk et al, 2019), for production of wheat with low gluten content (Sánchez-León et al, 2018), as required by people allergic to some components of gliadin in traditional wheat cultivars (Palosuo et al, 2001; Pastorello et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of enzyme activity in wheat showed that the enzymes in the wheat ear showed C 4 characteristics. Analysis of gene expression in the developing wheat grain showed expression of genes encoding C 4 photosynthesis in mid seed development [12] corresponding to the period of peak grain filling and maximal respiration to support starch and storage protein accumulation in the endosperm [45]. One misconception is that all genes necessary for C 4 photosynthesis are also present in C 3 genomes.…”
Section: C4mentioning
confidence: 99%
“…Yield is determined by the number and size of grains produced by the crop. The major genes controlling yield-related traits in wheat have been identified by genetic and genomics techniques, as reported in recent reviews [8587].…”
Section: Manipulating Agronomic Traits By Transgene Expression In mentioning
confidence: 99%